Relationship of Accreditation Status with Completeness of Medical Record Documents for Inpatients at the Hospital - Puji Lestari; Amalia Devi Fitriatama Arbi; Ismini Putri Robbaniyah; Devi Pramita Sari (Proceeding of International Conference on Science, Health, And Technology, 2021)
This research aims to analyze differences in the completeness of inpatient medical record documents before and after accreditation at Pandan Arang Hospital, Boyolali. The research method used in this research is a type of analytic study and a cross sectional study design. The results of this research were 9 inpatient medical record documents before accreditation with a percentage of 18% complete and 41 with a percentage of 82% incomplete. Meanwhile, in the completeness of medical record documents after accreditation as many as 16 with a percentage of 32% complete and 34 with a percentage of 68% incomplete. The completeness of medical record documents before and after accreditation has increased but in statistical calculations it does not increase but is significant, statistical tests using the chi-square test result in p value> 0.106 so that ha is rejected and ho is accepted, so there is no difference in the completeness of the medical record documents of hospitalized patients. stay before and after accreditation.